Given the ODE
(x - 1) y'' + y' = 0
we assume a solution of the form
[tex]y(x) = \displaystyle \sum_{n=0}^\infty c_n x^n[/tex]
with derivatives
[tex]y'(x) = \displaystyle \sum_{n=0}^\infty n c_n x^{n-1} = \sum_{n=0}^\infty (n+1) c_{n+1} x^n[/tex]
[tex]y''(x) = \displaystyle \sum_{n=0}^\infty (n+1) n c_{n+1} x^{n-1} = \sum_{n=0}^\infty (n+2)(n+1) c_{n+2} x^n[/tex]
Substituting these series into ODE gives
[tex]\displaystyle (x - 1) \sum_{n=0}^\infty (n+2)(n+1) c_{n+2} x^n + \sum_{n=0}^\infty (n+1) c_{n+1} x^n = 0[/tex]
[tex]\displaystyle \sum_{n=0}^\infty (n+2)(n+1) c_{n+2} x^{n+1} - \sum_{n=0}^\infty (n+2)(n+1) c_{n+2} x^n + \sum_{n=0}^\infty (n+1) c_{n+1} x^n = 0[/tex]
[tex]\displaystyle \sum_{n=1}^\infty (n+1)n c_{n+1} x^n - \sum_{n=0}^\infty (n+2)(n+1) c_{n+2} x^n + \sum_{n=0}^\infty (n+1) c_{n+1} x^n = 0[/tex]
[tex]\displaystyle \sum_{n=1}^\infty \bigg((n+1)n c_{n+1} - (n+2)(n+1) c_{n+2} + (n+1) c_{n+1}\bigg) x^n - 2c_2 + c_1 = 0[/tex]
[tex]\displaystyle \sum_{n=1}^\infty \bigg((n+1)^2 c_{n+1} - (n+2)(n+1) c_{n+2}\bigg) x^n - 2c_2 + c_1 = 0[/tex]
[tex]\displaystyle \sum_{n=0}^\infty \bigg((n+1)^2 c_{n+1} - (n+2)(n+1) c_{n+2}\bigg) x^n = 0[/tex]
Then the coefficients [tex]c_n[/tex] are given recursively by
[tex](n+1)^2 c_{n+1} - (n+2)(n+1) c_{n+2} = 0[/tex]
for all n ≥ 0, or equivalently,
[tex]c_{n+2} = \dfrac{n+1}{n+2} c_{n+1}[/tex]
which most closely resembles the second choice.